Síntese de carbonatos cíclicos a partir de CO2 e epóxidos catalisada por complexos metálicos com ligantes benzotiazois - Mata, Álvaro Farias Arruda da (2020)
Carbon dioxide is an abundant and renewable source of carbon, which can be used to replace fossil resources in the synthesis of various substances. This work aims to develop a catalytic system, using complexes with benzothiazole-derived ligands, for the synthesis of cyclic carbonates by the chemical fixation of CO2 by reaction with epoxides. The ligands 2-(2-hydroxyphenyl)-benzothiazole (L1) and 2-(2-pyridyl)-benzothiazole (L2) were used in the synthesis of eight complexes with the metals Zn(II) (7a and 8a), Co(II) (7b and 8b), Ni(II) (7c and 8c) and Mn(II) (7d and 8d). The synthesized compounds were characterized by nuclear magnetic resonance, elemental analysis, infrared and UV-vis absorption spectroscopy and thermal analysis. Initially, all complexes were active catalysts in the cycloaddition reaction between CO2 and propylene oxide for the production of the respective cyclic carbonate with high selectivity and conversions of 15% to 48%, under high pressure conditions. Under the same conditions, the control experiment converted only 2% of the epoxide. The catalytic system with complex Zn(L1)2 (8a) was the most active, so this complex was used in the optimization of the reaction by evaluating the following parameters: pressure, time, temperature, catalyst load and type of cocatalyst. The optimum condition was used in reactions with different epoxides, producing the respective cyclic carbonates with high conversion values. This is the first work to report a catalytic system that uses complexes with benzothiazole ligands for the synthesis of cyclic carbonates from CO2 and epoxides, demonstrating its efficiency in the chemical fixation of CO2.